Medicinal applications of coordination chemistry - Jones, Chris J. (Royal Society of Chemistry, 2007)
This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity. This product is not available separately, it is only sold as part of a set. There are 750 products in the set and these are all sold as one entity.
Keywords: Coordination compounds.; Pharmaceutical chemistry.; elektronické knihy; electronic books